Can pneumothorax developing in COVID-19 patients be a mortality marker? - KASAPOĞLU, UMUT SABRİ (My University, 2022)
Objectives: The purpose of this study is to investigate the effects of pneumothorax (PX), a rare complication of COVID-19, on mortality. Methods: All patients admitted to our hospital with the diagnosis of COVID-19 were screened, and patients who developed PX were included in the study. Patient demographics data, number of days of hospitalization for comorbidities, day and duration of thorax tube insertion, and laboratory findings during hospitalization were recorded by scanning the hospital automation system and patient records. Results: For our study, 7485 patients hospitalized with the diagnosis of COVID-19 were screened in intensive care unit. PX was detected in 32 (0.296%) of the patients. About 59.4% of these patients included in the study were male. DM was the most common comorbid condition at 56.3%. In these patients, the mortality rate was found to be 90.6%. Conclusion: The data obtained indicate that PX, a COVID-19 complication, leads to a serious increase in mortality. We believe that using protective ventilation methods to avoid the development of pneumotarax will help to reduce mortality.

Amaç: Çalışmamızda koronavirüs hastalığı-19’un (COVID-19) nadir görülen bir komplikasyonu olan pnömotoraksın mortalite üzerine etkisini araştırmayı amaçladık. Yöntem: Hastanemizde COVID-19 tanısı nedeniyle yatırılarak tedavi edilen tüm hastalar tarandı ve pnömotoraks gelişen hastalar çalışmaya dahil edildi. Hastaların demografik verileri, yandaş hastalıkları, yatış gün sayısı, toraks tüpünün takılış günü ve süresi, hastaneye yatış esnasında yapılan laboratuvar bulguları hastane otomasyon sistemi ve hasta dosyaları taranarak kaydedildi. Bulgular: Çalışmamız için COVID-19 tanısı ile hastanede yatarak tedavi gören 10.800 hasta tarandı. Çalışmaya dahil edilen 32 (%0,296) hastada pnömotoraks gelişti. Çalışmaya dahil edilen hastaların %59,4’ü erkekti. Yandaş hastalık incelendiğinde %56,3 ile diabetes mellitus en sık eşlik eden hastalıktı. Bu hastalarda mortalite oranı %90,6 olarak hesaplandı. Sonuç: Elde edilen veriler COVID-19 komplikasyonu olan pnömotoraksın ciddi mortalite artışına sebep olmaktadır. Koruyucu ventilasyon yöntemleri ile pnömotoraks gelişiminin önlenmeye çalışılmasının mortalitenin azaltılmasına katkı sağlayacağını düşünmekteyiz.
Keywords: COVID-19; mortality; pneumothorax; mortalite; pnömotoraks